(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Exposures along open quarries located in the eastern Cametá Sub-Basin provide an opportunity of further discussing the depositional environments of the Upper Cretaceous-?Lower Tertiary Ipixuna Formation. The lower part of this unit emphasized herein, known as the "soft kaolin", consists mostly of kaolinitized sandstones and mudstones with well preserved sedimentary structures that are particularly favorable for facies analysis and paleoenvironmental reconstructions. The sandstones are chiefly cross-stratified, typically with low angle, locally reverse orientated foresets with reactivation surfaces and/or mud drapes. These characteristics, together with a trace fossil assemblage consisting of Ophiomorpha, Thalassinoides, Planolites, Teichichnus, Taenidium and Skolithos, conform to deposition in a coastal setting influenced by tidal processes. Although a previous study has documented tidal processes during deposition of the soft kaolin (Santos Jr. and Rossetti, 2003), this paper shows that the influence of tidal currents was much more important than initially proposed. Hence, the kaolinitized deposits are attributed to tidally influenced fluvial channel (Facies Association A), tidal channel (Facies Association B), tidal flat/mangrove (Facies Association C), and tidal sandy bar/tidal sandy flat (Facies Association D), all together comprising a tide-dominated estuarine system.